1991
DOI: 10.1128/aac.35.5.1008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of beta-lactamase production in Pseudomonas aeruginosa biofilm

Abstract: Imipenem induced high levels of beta-lactamase production in Pseudomonas aeruginosa biofilms. Piperacillin also induced beta-lactamase production in these biofilms but to a lesser degree. The combination of beta-lactamase production with other protective properties of the biofilm mode of growth could be a major reason for the persistence of this sessile bacterium in chronic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(100 citation statements)
references
References 14 publications
3
92
0
4
Order By: Relevance
“…Limited diffusion can also protect biofilms from degradable antimicrobials. Indeed, P. aeruginosa produces AmpC ␤-lactamase, and it has been demonstrated that 2.5% of clinical isolates from CF patient sputa are totally derepressed, with a high basal level of enzyme production that can be increased further through ␤-lactam-mediated induction and ␤-lactamase accumulation in the biofilm matrix (49,50). In clinical samples, insertion sequences inactivating the ampD gene have been described for CF patients with constitutively high expression of ␤-lactamase (51).…”
Section: Biofilm Recalcitrance Is Multifactorialmentioning
confidence: 99%
“…Limited diffusion can also protect biofilms from degradable antimicrobials. Indeed, P. aeruginosa produces AmpC ␤-lactamase, and it has been demonstrated that 2.5% of clinical isolates from CF patient sputa are totally derepressed, with a high basal level of enzyme production that can be increased further through ␤-lactam-mediated induction and ␤-lactamase accumulation in the biofilm matrix (49,50). In clinical samples, insertion sequences inactivating the ampD gene have been described for CF patients with constitutively high expression of ␤-lactamase (51).…”
Section: Biofilm Recalcitrance Is Multifactorialmentioning
confidence: 99%
“…The proposed mechanism for resistance is that the glycocalyx may create a diffusion barrier to the antimicrobial agent de Beer et al, 1994;Chen and Stewart, 1996;Giwercman et al, 1991;Liu et al, 1998;Stewart et al, 1998). Diffusion through a biofilm may be affected by charge (ionic) interactions between the glycocalyx and the antimicrobial agent, by an increase in the distance the agent must diffuse, by molecular sieving (size exclusion), and by the viscosity of the glycocalyx.…”
Section: Limited Diffusion Through the Biofilmmentioning
confidence: 99%
“…Biofilm structure can prevent an applied antimicrobial agent from reaching the entire bacterial population by mechanisms such as a neutralizing reaction with components of the biofilm [29,10], synthesis of an antimicrobial degrading enzyme [16,3] and adsorption of the antimicrobial by the exo-polymeric substance (EPS) [19]. There have been several mathematical models of biofilm disinfection that include diffusion and various antimicrobialdegrading reactions [25,12,6].…”
Section: Introductionmentioning
confidence: 99%